2006
DOI: 10.1161/circulationaha.105.560649
|View full text |Cite
|
Sign up to set email alerts
|

Increased Peripheral Chemoreceptors Sensitivity and Exercise Ventilation in Heart Transplant Recipients

Abstract: Background-Heart failure is characterized by increased ventilation during exercise, which is positively related to increased peripheral and central chemoreceptor sensitivity. Heart transplantation does not normalize the ventilatory response to exercise, and its effects on the chemoreflex control of ventilation remain unknown. We tested the hypothesis that chemoreceptor sensitivity is increased in heart transplant recipients (HTRs) and linked to exercise hyperpnea. Methods and Results-We determined the ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…Similarly, other clinical studies (Haque et al 1996,van de Borne et al 1996 reported that suppression of peripheral chemoreceptor activity by hyperoxia had no effect on muscle sympathetic nerve activity or arterial pressure. By contrast, other groups ,Ponikowski & Banasiak, 2001,Ciarka et al 2006 have found an enhanced ventilatory response to hypoxia in CHF patients, particularly those in more severe stages of heart failure. In addition, heightened peripheral chemoreflex function correlates significantly with the enhanced ventilatory response to exercise and dyspnea observed in these patients (Chua et al 1997,Ciarka et al 2006).…”
Section: Chemoreflex Control Of Sympathetic Function In Heart Failurementioning
confidence: 78%
See 1 more Smart Citation
“…Similarly, other clinical studies (Haque et al 1996,van de Borne et al 1996 reported that suppression of peripheral chemoreceptor activity by hyperoxia had no effect on muscle sympathetic nerve activity or arterial pressure. By contrast, other groups ,Ponikowski & Banasiak, 2001,Ciarka et al 2006 have found an enhanced ventilatory response to hypoxia in CHF patients, particularly those in more severe stages of heart failure. In addition, heightened peripheral chemoreflex function correlates significantly with the enhanced ventilatory response to exercise and dyspnea observed in these patients (Chua et al 1997,Ciarka et al 2006).…”
Section: Chemoreflex Control Of Sympathetic Function In Heart Failurementioning
confidence: 78%
“…By contrast, other groups ,Ponikowski & Banasiak, 2001,Ciarka et al 2006 have found an enhanced ventilatory response to hypoxia in CHF patients, particularly those in more severe stages of heart failure. In addition, heightened peripheral chemoreflex function correlates significantly with the enhanced ventilatory response to exercise and dyspnea observed in these patients (Chua et al 1997,Ciarka et al 2006). …”
Section: Chemoreflex Control Of Sympathetic Function In Heart Failurementioning
confidence: 78%
“…In HF animal models, the augmented sympathetic drive during hypoxia is largely influenced by the tonic excitatory influence of peripheral chemoreflex activity. 20,21 In humans, van de Borne et al 22 showed that tonic chemoreflex activation does not contribute to elevated MSNA in HF patients, whereas Ponikowski et al 23 observed that HF patients with peripheral chemoreceptor hypersensitivity were those with a poor outcome. Our study suggests that anemia, in combination with CHF, could lead to chemoreflex-related sympathetic overactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, carotid body chemosensitivity plays a dominant role in constraining variations of arterial pH in response to the acute metabolic acidosis induced by heavy exercise (19). Previous studies on chronic heart failure patients have demonstrated that the exaggerated response from peripheral chemoreceptors leads to a rapid ventilator augmentation, albeit with lower ventilatory efficiency, during exercise (18)(19)(20).…”
Section: The Carotid Body Chemoreflexes and Ventilatory Responsementioning
confidence: 99%